A methodology for the heuristic optimization of solvent-based CO2 capture processes when applied to new flue gas compositions: A case study of the Chilled Ammonia Process for capture in cement plants. (November 2020) - Pérez-Calvo, José-Francisco; Sutter, Daniel; Gazzani, Matteo; Mazzotti, Marco
Highlights: Optimization for new flue gas characteristics and/or process specifications. Model calibration based on mass transfer properties avoids new experimental campaigns. Process sections are added step-by-step for process optimization. Rate-based and equilibrium-based simulations using Murphree efficiencies are combined. Conditions that minimize energy consumption and maximize productivity are found. Abstract: Solvent-based post-combustion CO2 capture technologies are key to timely decrease industrial CO2 emissions. However, the flue gas composition differs among different industries so that different optimal operating conditions are expected. This work provides a methodology to determine the operating conditions that minimize energy consumption and maximize productivity of the capture process, for given flue gas composition and process specifications, while keeping the time required for process development at a minimal level. Firstly, it carries out a comprehensive selection and calibration of the model. Secondly, it applies a step-wise heuristic optimization procedure. In this work, this methodology has been demonstrated by means of the Chilled Ammonia Process (CAP) applied to cement plants. The optimal CAP operation has led to reboiler duties as low as 2.1 MJ th kg CO 2 captured - 1, while maintaining the productivity of the CO2 absorber, thus the column height, at values similar to those typical of the power plant application.